Prospecção de produtos naturais para o manejo integrado de Lasioderma serricorne (Fabricius, 1792) (Coleoptera: Anobiidae) - Silva, Ana Paula Oliveira da (2017)
Lasioderma serricorne (F.) (Fabricius, 1792) (Coleoptera: Anobiidae) is a cosmopolitan plague popularly known as a tobacco beetle that attacks a wide variety of stored agricultural products, like soybeans, escavating galleries in the grains while feeding and consequently generating losses to the producers by the loss of quality and value of the seeds. Due to the risks of intoxication and environment contamination with chemical residues, as well as the emergence of resistant individuals, other approaches to the control of L. serricorne have been sought. The host plant kairomones are molecules with potential for application as food attractants in traps for monitoring and capture insects. On the other hand, the evaluation of essential oils (EO) of native plants cultivated locally, can contribute to the discovery of useful compounds as natural repellents or bio-insecticides, also generating tools useful in integrated pest management (IPM). The objective of this study was to investigate and identify the volatile organic compounds released by stored soybeans from 3 varieties cultivated in Brazil with attractiveness to adults L. serricorne (soybean marketed in large supermarket chains in Maceió-AL and two varieties EMBRAPA BRS284 and BRS360RR) and to test the EO activity of the mature fruits of Schinus terebinthifolius, in order to promote the prospection of natural compounds with potential for application in the integrated management of this pest in storage environments. The attractiveness of grains and extracts prepared by dynamic headspace collection was evaluated in 4-arm olfactometer behavioral bioassays, while the isolation and identification of the bioactive compounds were carried out using gas chromatography coupled to electroanthennography (GC-EAG) and gas chromatography coupled to mass spectrometry (GC-MS). Five EAG-active compounds were identified in the extracts of soybeans: 1-octen- 3-ol, 3-octanol, 1- nonanol, linalool and limonene. The behavioral response of L. serricorne in 4-arm olfactometer bioassays to synthetic compounds was statistically significant for 1- octen-3- ol, 3-octanol, 1-nonanol and linalool, while the attraction for the 4 synthetic blend was comparable to that verified for soybeans. The activity of the EO extracted by steam-drag of the mature fruits of S. terebinthifolius (3 replicates) harvested from matrices located on the A. C. Simões Campus of UFAL, Maceió-AL, on L. serricorne adults was tested in 4-arm olfactometer bioassays , in two concentrations (1 and 10 μL), while the EO composition was analyzed by GC-FID and GC-MS. EO repellency was checked at a dose of 10 μL. A total of 14 compounds were identified in S. terebinthifolius EO, with the main components being β-pinene (49.8%), α-pinene (33.49%), 3-carene (5.85%), germacrene-D (2.08%) and bornylene (1.21%). The attractive compounds identified from the soybean grains act as kayromones for L. serricorne, while the S. terebinthifolius EO has repellent activity against this pest, so the results obtained here can be applied in the development of bioproducts for the integrated management of L. serricorne in and around storage environments, favoring the rational use of insecticides.